Efficient Moving Target Tracking Algorithm: Design and Implementation of the Sand-Table Tracking Algorithm - Li, Jia Qi (Applied Mechanics and Materials, 2013)
Working on the design of a new algorithm :sand_table algorithm.The algorithm could work well in recognizing and tracking an single moving target shot by camera or in a video .The algorithm works simple with low operation cost.May used in tracking different object of many kinds.The algorithm imitate the the process of falling sands to Greatly enhance the tracking ability and tracking accuracy.